2014
DOI: 10.1159/000358838
|View full text |Cite
|
Sign up to set email alerts
|

Low Serum Allopregnanolone Is Associated with Symptoms of Depression in Late Pregnancy

Abstract: Background: Allopregnanolone (3α-hydroxy-5α-pregnan-20-one) is a neurosteroid which has an inhibitory function through interaction with the GABAA receptor. This progesterone metabolite has strong sedative and anxiolytic properties, and low endogenous levels have been associated with depressed mood. This study aimed to investigate whether the very high serum allopregnanolone levels in late pregnancy covary with concurrent self-rated symptoms of depression and anxiety. Methods: Ninety-six women in pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
50
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(62 citation statements)
references
References 48 publications
3
50
1
1
Order By: Relevance
“…Significant research links low levels of allopregnanolone to depressed mood Eser et al, 2006;Le Melledo and Baker, 2004;Padberg et al, 2002;Pinna et al, 2006;Schule et al, 2014;Strohle et al, 1999;Uzunova et al, 2006) and other evidence links mood states or histories thereof with alterations in the ratio of allopregnanolone to its precursors (Girdler et al, 2012;Schiller et al, 2014). In the perinatal period specifically, Deligiannidis et al (2013), in a small sample, found no relationship between pregnancy allopregnanolone and the development of PPD, whereas Hellgren et al (2014) found significantly lower levels of allopregnanolone in depressed pregnant women when compared with healthy controls (Hellgren et al, 2014). In a separate analysis, our group found that low levels of allopregnanolone measured in the second trimester predicted the development of PPD (p = 0.01); this effect was driven by women who were euthymic in the second trimester (Osborne et al, under review).…”
Section: Discussionmentioning
confidence: 99%
“…Significant research links low levels of allopregnanolone to depressed mood Eser et al, 2006;Le Melledo and Baker, 2004;Padberg et al, 2002;Pinna et al, 2006;Schule et al, 2014;Strohle et al, 1999;Uzunova et al, 2006) and other evidence links mood states or histories thereof with alterations in the ratio of allopregnanolone to its precursors (Girdler et al, 2012;Schiller et al, 2014). In the perinatal period specifically, Deligiannidis et al (2013), in a small sample, found no relationship between pregnancy allopregnanolone and the development of PPD, whereas Hellgren et al (2014) found significantly lower levels of allopregnanolone in depressed pregnant women when compared with healthy controls (Hellgren et al, 2014). In a separate analysis, our group found that low levels of allopregnanolone measured in the second trimester predicted the development of PPD (p = 0.01); this effect was driven by women who were euthymic in the second trimester (Osborne et al, under review).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies had been shown that lowered allopregnanolone levels in patients might lead to an imbalance in excitatory neurotransmission that cause anxiety and depressive symptoms (Hellgren et al, 2014). Conversely,…”
Section: Introductionmentioning
confidence: 99%
“…Allopregnanolone concentrations increase during pregnancy and fall rapidly post partum. Women with higher depression scores in late pregnancy have been found to have lower serum concentrations of allopregnanolone 69. Furthermore, in an exploratory study of 60 pregnant women with a previous diagnosis of mood disorder, higher concentrations of allopregnanolone during the second trimester were associated with a 63% (95% confidence interval 13% to 84%) reduction in the risk of developing postpartum depression (P=0.02) 70.…”
Section: Personalized Treatment For Specific Clinical Characteristicsmentioning
confidence: 96%